LESS INCLUSIVE GROWTH IN INDONESIA? THE UNINTENDED CONSEQUENCES OF INTERNET PENETRATION - Jamil, Hidsal (Fakultas Ekonomi dan Bisnis, UNTAN, 2022)
Separate studies on the impact of internet penetration on growth and per capita income levels, inequality, and poverty levels are still being discussed. Using data from 33 Indonesian provinces between 2008 and 2020, this paper investigates whether internet penetration modulates economic growth by reducing inequality and poverty. The Two-Way Fixed Effect (TWFE) econometric model was used. Two findings can be concluded from this paper. First, Indonesia's economic growth remains less inclusive, as evidenced by rising per capita income, which tends to reduce poverty but not income inequality. Second, Indonesia's economic growth tends to be less inclusive as an unintended consequence of internet penetration. Although it strengthens the effect on poverty reduction, on the other hand, the interaction of economic growth with internet penetration tends to exacerbate income inequality. Based on these findings, the study suggests that the government should improve advanced ICT skills and lower barriers to internet adoption, particularly for the less fortunate. The internet is expected to become a tool to achieve inclusive growth through expanding a newly established middle class instead of simply the economic transformation of the poor into non-poor households under this policy.